The Role of Natural Gas in Achieving Sustainable Development Goals - Aksyutin, Oleg E.; Ishkov, Alexander G.; Romanov, Konstantin V.; Grachev, Vladimir A. (International Journal of Energy Economics and Policy, 2020)
Natural gas started to have an increasingly tangible impact on human civilization in the second half of the 20th century, and today it has come to the forefront, affecting the implementation of practically all Sustainable Development Goals. In this work, the systemic analysis of the natural gas influence on sustainable development not only for specific purposes but also for pillars of sustainable development has been conducted: economic development, social sphere, and environmental protection, which in cooperation generate allowable, fair and acceptable states. As a result of the analysis, it has been found that natural gas, unlike other types of fuel and nonfuel sources of energy, possesses the highest rates of all three states, and it is the most powerful means for Sustainable Development Goals achievement both at the present and, in combination with nature-like technologies of obtaining energy, in the future sustainable development of human civilization. Keywords: natural gas; sustainable development; sustainable development goals; sustainable development state; nature-like energy sources; energy power. JEL Classifications: Q400, Q480, Q490, Q540 DOI: https://doi.org/10.32479/ijeep.9359